Pore geometry effects on intrapore viscous to inertial flows and on effective hydraulic parameters. Issue 2 (12th February 2013) - Chaudhary, Kuldeep; Cardenas, M. Bayani; Deng, Wen; Bennett, Philip C.
Key Points Pore geometry factor β can predict hydraulic conductivity K Hydraulic conductivity is controlled by local friction drag near pore throats β is indicator of non‐linear characteristics during Forchheimer flows